FACTORS INFLUENCING UNDER-REPORTING OF FINANCIAL PERFORMANCE AMONG STUDENT LUBS AND ASSOCIATIONS - Mohd Syazwan Karim; Khairiah Ahmad; Nur Farahah Mohd Pauzi; Azlan Md Thani; Adriana Shamsudin; Nurfarahin Roslan (International Journal of Accounting, Finance and Business, 2022)
This paper aims at understanding factors that contribute to under-reporting offinancial performance among student clubs and associations. Accounting information is notimportant for business only, but it is also essential for clubs and associations to plan andmanage their financial matters more effectively. However, most student clubs and associationsdo not keep a proper book of accounts since there is no legal obligation to do so. Anotherreason is because they perceive accounting is a very difficult process due to the lack of exposurein providing accounting records particularly for non-accounting students. Using qualitativeresearch design, semi-structured interviews were conducted with 13 students who were therepresentatives of 13 different clubs and associations from a tertiary institution in Melaka,Malaysia. Results show lack of accounting knowledge, inadequate training and poor sourcedocument keeping are the key factors influencing under-reporting of financial performanceamong these student clubs and associations. Investigating the issues that contribute to underreporting of financial performance by the clubs and associations would be useful for theuniversity Student Affairs Division in designing appropriate training to improve the clubtreasurers’ financial reporting.